The Impact of Task Context on Pleasantness and Softness Estimations: A Study Based on Three Touch Strategies - Binyue Gao; Yinghua Yu; Yoshimichi Ejima; Jinglong Wu; Jiajia Yang (Behavioral Sciences)
This study investigated the two distinct perceptions (pleasantness and softness) of deformable stimuli with different degrees of compliance under conditions with and without a contextual task. Three tactile strategies—grasping, pinching, and pressing—were used to perceive the stimuli. In Experiment 1 (without a contextual task), participants estimated the perceived intensity of softness or pleasantness for each stimulus. In Experiment 2 (with a contextual task), the participants sequentially perceived two stimuli with different compliance levels and indicated which stimulus they perceived as softer and pleasant. The results showed that the psychophysical relationship between compliance and perceived softness was consistent across all tactile strategies in both experiments, with softness estimates increasing as compliance increased. However, the relationship between compliance and pleasantness differed between the two experiments. In Experiment 1, pleasantness estimates increased monotonically with increased compliance. However, in Experiment 2, across all tactile strategies, pleasantness began to decrease within the compliance range of 0.25–2.0 cm2/N, exhibiting an inverted U-shaped trend. These findings indicate that the relationship between compliance and pleasantness is task-dependent, particularly demonstrating significantly different trends when a contextual task is introduced. In contrast, the relationship between compliance and softness remained consistently monotonic.